COMPARATIVE STUDY OF MEDIATION IMPLEMENTATION IN INDONESIA AND TURKEY - Muhamad Ali Muhsim; Erfaniah Zuhriah; Ali Hamdan (Universitas Islam Negeri Alauddin Makassar, 2022)
Mediation as an alternative dispute resolution has its advantages. However, behind the advantages of dispute resolution, it is inversely proportional to the data on the success of mediation in Indonesia which is very low. Based on statistical data from the Semarang Religious Court during 2015-2019, less than 3% of mediations were successful. However, the data on the success of mediation in Indonesia contradicts that of Turkey. During 2017, more than 80% of cases were successfully resolved through mediation. Based on this data, it is necessary to compare the implementation of mediation between Indonesia and Turkey. This research is included in normative juridical research with a qualitative comparative approach. The results of this study indicate that there are similarities and differences in the implementation of mediation between Indonesia and Turkey. The equation lies in the terms of the mediator, the number of mediators and the place. The difference lies in regulation, mediation time, disputes that must be mediated, mediation implementation, mediator title, mediation fees, mediator audit, mediator membership fees and the strength of the peace deed